2023
DOI: 10.1002/fft2.270
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of the effect of four polysaccharides on intestinal bacteria of mice with colitis

Abstract: Polysaccharides are typically resistant to digestion in the gastrointestinal tract and are instead degraded by gut microbiota in the colon. As such, they are commonly employed as carriers for colon‐targeted drugs, with the potential to regulate gut microbiota. Pectin, carrageenan, guar gum, and xanthan gum are commonly used polysaccharide carriers, but their degradation in the gut microbiota under colitis conditions as well as their effects on gut microbiota remains unclear. In this study, we performed the in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 51 publications
0
2
0
1
Order By: Relevance
“…In our previous study, we demonstrated the robust growth performance of C. tyrobutyricum when utilizing chitooligosaccharides (COSs) as the exclusive carbon source or in conjunction with glucose as a mixed carbon source. , Building upon this finding, we conducted a comprehensive assessment of the effects of the synbiotic containing C. tyrobutyricum and COSs in a mouse model of IBD induced by dextran sulfate sodium (DSS).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our previous study, we demonstrated the robust growth performance of C. tyrobutyricum when utilizing chitooligosaccharides (COSs) as the exclusive carbon source or in conjunction with glucose as a mixed carbon source. , Building upon this finding, we conducted a comprehensive assessment of the effects of the synbiotic containing C. tyrobutyricum and COSs in a mouse model of IBD induced by dextran sulfate sodium (DSS).…”
Section: Introductionmentioning
confidence: 95%
“…In our previous study, we demonstrated the robust growth performance of C. tyrobutyricum when utilizing chitooligosaccharides (COSs) as the exclusive carbon source or in conjunction with glucose as a mixed carbon source. 19,20…”
Section: ■ Introductionmentioning
confidence: 99%
“…Estes resultados fornecem orientação teórica para a seleção de transportadores de medicamentos para o tratamento de doenças inflamatórias intestinais e fornecem informações sobre a relação entre polissacarídeos e a microbiota intestinal. Zhang et al, 2023. Fonte: Dados da pesquisa (2023).…”
Section: Propriedades Mucoadesivasunclassified